(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Backround: College students are a unique population occupying a middle ground between childhood and adulthood, between work and leisure, they have been at the forefront of social change. Use of the internet is a part of college students’ daily routine, in part because they have grown up with computer. It is integrated into their daily communication habits and has become a technology as ordinary as the telephone or television. Therefore, an information-proficient workface that is computer literate, trained in information management skills and motivated to use the well designed clinical systems would be necessary in tertiary institutions to help students in their learning process. Objectives:(1) To find out duration and frequency of internet use among medical students of GSVM Medical college. (2)To explore the pattern of usage in terms of type of work done through internet. (3)To find out the barriers, if any, in using information technology. (4)Based on findings, to give suggestions for enhancing the use of computers and internet in positive direction for medical students. Materials and methods: This is Cross-sectional, institution based study carried out in medical students of G.S.V.M.Medical College for duration of 3 months from October 2018 to December 2018.A total of 400 students will be studied.No sampling technique was implicated as all students were included in our study. A pre-designed & pre-tested questionnaire was used. The questions consisted of details regarding bio-social characteristics , duration & amount of internet and computer use, type of work performed on computer and the barriers ,if any in usage of the same. Results: Among the pre clinical year students,66.7% of students used internet for academic purpose, 62.5% of students use internet for social networking,about48.2% of students use internet for downloading movies, 31.9% & 58.5% for news, games. Nearly 66.5%of the students use it for banking, shopping, & for online entertainment. Only 19.7% used it for literature search. 19.1% of students use internet less than three hours a week and only 80.9% of students use internet more than three hours a week. Among the para clinical year students, 74.8% of students used internet for academic purpose , 52.7% of students use internet for social networking,about43.3% of students use internet for downloading movies, 27.5% & 54.3% for news, games. students 63.8% of students use internet less than three hours a week and 36.2% of students use internet more than three hours a week.